Genetic diversity analysis and fingerprint construction of Korean pine (Pinus koraiensis) clonal seed orchard - Yan, Pingyu; Xie, Zixiong; Feng, Kele; Qiu, Xinyu; Zhang, Lei; Zhang, Hanguo (Frontiers in Plant Science, 2023)
Korean pine is a native tree species in Northeast China. In order to meet the needs of germplasm resource evaluation and molecular marker-assisted breeding of Korean pine, we collected Korean pine clones from 7 populations in Northeast China, analyzed the genetic diversity and genetic structure by SSR molecular marker technology and clustered them to revealed the inter- and intrapopulation differentiation characteristics of each clone. The fingerprint profiles of 161 Korean pine clones were also constructed. 77 alleles were detected for 11 markers, and 18 genotypes were identified on average for each marker. The PIC of the different markers ranged from 0.155-0.855, and the combination of PI and PIsibs for the 11 markers was 3.1 × 10-8 and 1.14 × 10-3, respectively. MANOVA showed that genetic variation existed mainly within populations, accounting for 98% of the total variation. The level of genetic differentiation among populations was low, with an average Nm between populations of 11.036. Genetic diversity is lower in the Lushuihe population and higher in the Tieli population. The 161 Korean pine clones were divided into 4 or 7 populations, and the 7 populations were not clearly distinguished from each other, with only the Lushuihe population showing partial differentiation. There is no significant correlation between the genetic distance of Korean pine populations and the geographical distance of their superior tree sources. This result can provide recommendations for future Korean pine breeding programs. The combination of 11 markers could completely distinguish 161 clones and establish the fingerprint. Genetic diversity of Korean pine clones from the 7 populations was abundant, and the genetic distances of individuals and populations were evenly dispersed. The fingerprint map can be used for the identification of Korean pine clones.